Principles and rules governing evidence activity - González Castro, Manuel Antonio (2021)
There is some conceptual or essential difference between principles and procedural rules, and if any, should also be given on the principles and rules governing the confirmatory activity, and often confused doctrine has to treat the area of general process theory. That is why we propose in this paper to identify those that doctrine called "early evidence" or "general principles of judicial proof" in order to be achieved by proper conceptualization, identify if we have a procedural rule or to the particular application of a procedural principle. Also discuss some claims that under the guise of a probationary linguistic principle actually hide an ideological preference or axiological incompatible with the procedural system devised by the Constitution, due process embodied in the International Covenants, if not with the reality of the phenomenon procedural.